The WNT/beta-catenin pathway : Profibrotic signaling in fibroblasts in idiopathic pulmonary fibrosis - Kramer, Monika; Justus Liebig University Giessen (My University, 2010)
Idiopathic pulmonary fibrosis (IPF) is the most common and most severe form of theidiopathic interstitial pneumonias (IIP). Unresponsive to any currently available therapy itleads to architectural distortion of the lung parenchyma and rapidly to respiratory failure.Although the pathogenesis of the disease is not completely understood, it is well accepted thatinitial alveolar epithelial cell injury is followed by enhanced fibroblast proliferation andactivation to myofibroblasts. These fibroblasts are considered as key effector cells in IPF. Theso called fibroblast foci represent hallmark lesions of the disease as they are responsible forthe increased ECM deposition that leads to impaired gas exchange and ultimately to fibrosis.The present study aimed to reveal possible profibrotic paracrine effects of recently identifiedprofibrotic mediators that trigger the disturbed crosstalk between alveolar epithelial cells typeII (ATII) and fibroblasts. Recently, WNT/beta-catenin signaling has been demonstrated to beinvolved in the pathogenesis of IPF. In particular it has been reported that WNT3a andWNT1-inducible signaling protein (WISP) 1 are secreted by ATII cells in IPF.In the present project it was hypothesized that WNT3a and WISP1 act in a paracrine fashionon fibroblasts, thereby contributing to the impaired ATII cell ̶ fibroblast crosstalk in thepathogenesis of IPF.It was shown that active WNT/beta-catenin signaling takes place in NIH-3T3 fibroblasts in vitroas assessed by Western Blot analysis and quantitative RT-PCR. To reveal functional effects ofactive WNT/beta-catenin signaling, thymidine [H3] incorporation proliferation assay,immunofluorescence, Sircol Collagen Assay, as well as quantitative (q) RT-PCR wereperformed.WNT3a stimulation of fibroblasts caused a significantly increased production of theextracellular matrix component collagen and led to transcriptional upregulation of fibroblastactivation markers. Interestingly, WNT3a stimulation did not affect fibroblast proliferation.The paracrine effects of WISP-1, which is encoded by a WNT target gene, were analyzed in acomparable way. Like WNT3a, WISP-1 led to enhanced collagen deposition as well asupregulation of fibroblast activation markers. Proliferation of the fibroblasts remainedunaffected.These results provided evidence that both molecules, WNT3a and WISP1, are capable ofactivating lung fibroblasts and causing increased collagen production in these cells. Thereforeit is strongly suggested that WNT3a and WISP-1, which are aberrantly secreted by ATII cellsin IPF, are profibrotic mediators that act in a paracrine fashion on fibroblasts during thepathogenesis of this fatal disease.

Die idiopathische pulmonale Fibrose (IPF) ist die häufigste und schwerwiegendste Form deridiopathische interstitiellen Pneumonien (IIP). Sie ist therapierefraktär, führt zu Zerstörungder Architektur des Lungenparenchyms und rasch zu respiratorischem Versagen.Die Pathogenese der Erkrankung ist größtenteils ungeklärt, wobei neue Studien eine initialeSchädigung von Alveolarepithelzellen (AT) vermuten lassen, woraufhin es zu gesteigerterFibroblastenproliferation und Aktivierung von Fibroblasten in so genannten Fibroblasten Focikommt. Diese Foci sind für die gesteigerte Produktion extrazellulärer Matrix verantwortlich,welche zum fibrotischen Umbau des Gewebes führt.Das Ziel der vorliegenden Studie war es, mögliche Effekte bereits identifizierterprofibrotischer Mediatoren zu untersuchen, die die Kommunikation zwischen AT II Zellenund Fibroblasten stören.Kürzlich konnte gezeigt werden, dass der WNT/beta-catenin Signalweg in der Pathogenese derIPF eine Rolle spielt. Insbesondere wurde gezeigt, dass WNT3a sowie das WNT1-induciblesignaling protein-1 (WISP-1) im Rahmen der IPF von ATII Zellen sezerniert werden.Für das hier vorgestellte Projekt wurde die Hypothese aufgestellt, dass WNT3a und WISP1parakrin auf Fibroblasten wirken und somit zur gestörten Kommunikation zwischen ATIIZellenund Fibroblasten im Rahmen der Pathogenese von IPF beitragen.Mittels Western Blot Analyse und quantitativer RT-PCR konnte gezeigt werden, dass derWNT/beta-catenin Signalweg in NIH-3T3 Fibroblasten in vitro aktiviert werden kann. WeitereEffekte einer Aktivierung des WNT/beta-catenin Signalwegs wurden mittels Thymidin [H3]Proliferations Assay, Immunfluoreszenz, Sircol Collagen Assay und quantitativer RT-PCRdurchgeführt.WNT3a führte zu einer deutlich erhöhten Kollagenproduktion. Zudem kam es zu einererhöhten Transkription von typischen Markern einer Fibroblastenaktivierung.Interessanterweise beeinflusste WNT3a die Fibroblastenproliferation nicht. Die parakrinenEffekte von WISP-1, welches von einem WNT Targetgen kodiert wird, wurden ebenfallsuntersucht. Vergleichbar mit WNT3a führte WISP-1 zu einer erhöhten Kollagenbildung undFibroblastenaktivierung. Die Proliferationsrate der Fibroblasten änderte sich hingegen nicht.Die vorliegenden Ergebnisse zeigen, dass beide Proteine, WNT3a und WISP-1, zu einerAktivierung sowie einer erhöhten Kollagenproduktion von Lungenfibroblasten führenkönnen. WNT3a und WISP-1, welche in IPF verstärkt von ATII Zellen sezerniert werden,wirken parakrin auf Fibroblasten und stellen somit bedeutende profibrotische Mediatoren inder Pathogenese der IPF dar.
Der WNT/beta-catenin Signalweg
Keywords: ddc:610